Gender policy implementation process in higher education institutions in Ghana - Abnory, Sophia Agyeibea; Yin, Elijah Tukwariba; Boatbil, Christopher Sormiteyema (Masyarakat, Kebudayaan dan Politik, 2024)
To achieve gender equality, domestic and international organisations have developed gender policies to integrate gender equality considerations into development processes. However, gender inequality persists in most spheres of society. Some higher education institutions have developed and implemented gender policies to address the gender gap. The scholarly literature available pays scant attention to how gender policies are implemented in higher learning institutions. This study, therefore, aims to understand how gender policies in higher education institutions are implemented to bridge the gender gap in female participation and representation in leadership positions. Using the qualitative approach of in-depth interviews, the analysed data reveal that universities use various strategies such as mentoring female staff, gender awareness and sensitisation, creation of gender centres and institutional support, and continuous gender education as means of implementing gender policies. These strategies lead to resilient and gender-inclusive systems and promote full participation of women in the various sectors and subject areas of higher education in Ghana. It is concluded that effective implementation of gender policies in higher education institutions, through well-articulated strategies, is crucial for promoting female participation, challenging ingrained gender norms, and achieving gender equality and inclusivity.